Beyond Budgeting dalam Pemodelan Mitigasi Risiko Fiskal Daerah: Studi di Pemerintah Daerah Kabupaten Bondowoso Provinsi Jawa Timur - Suryawati, Dina; Anwar, Anwar; Suharsono, Agus; Rohman, Hermanto; Firdaus, Alfareza (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2023)
The low level of regional fiscal independence can result in pressure and fiscal risks for the central and regional governments. Local governments need to have an adaptive organizational system to mitigate fiscal risks for their regions. This study aims to design an early warning system to monitor local government fiscal risks through an adaptive fiscal risk mitigation model. This research was conducted in two stages: first, identifying the level of regional fiscal risk using the content analysis method, and second, designing a risk mitigation model using the Soft System Methodology (SSM). The results of this study indicate that all the fiscal risk indicators studied (financial, economic, social, institutional, and environmental) have high-value risk items. The fiscal risk mitigation model resulting from this research is through the beyond budgeting conception, which focuses on the structure of the institutional system. A self-organizational framework and a bottom-up system are the two main elements that drive the beyond-budgeting institutional ecosystem as fiscal risk mitigation. The self-organizational framework can be built through the supportive leader, organizational network, and market coordination subsystems—the bottom-up system-building subsystem, namely through resources on demand, public focus, and relative targets.